Consumo de álcool entre universitários: histórico de violência como risco e religião como fator de proteção - Priolo Filho, Sidnei Rinaldo (Universidade Federal de São Carlos, 2013)
Alcohol consumption among College students has been a main concern among different sectors of society around the world. Risk factors associated to this behavior are not clear and more research is needed. The objective of this research is to verify if a history of intrafamilial violence is associated to higher alcohol consumption during College years. Furthermore, analyze if religion has an association with the consumption among this group as well. A review of the literature points out that history of violence is associated with higher alcohol consumption, however few researches were made analyzing polyvictimization and future alcohol consumption. The consequences for children that suffered different forms of victimization are not yet known in full extension. This research tries to fill some of those blanks, for that purpose it used the AUDIT questionnaire adapted with 1452 participants. In that sample alcohol consumption in life had a percent of 93.51% to woman and 93.10% to men. While, the consumption in the last 3 month was 82.04% and 83,74% respectively. The most frequent form of violence was physical (40.99%), the second was exposure to domestic violence (30.60%). A linear regression model was performed and was found and association between having a history of violence and a higher score in alcohol consumption. That association was verified to all forms of violence, including polyvictimization. About religion, results shown that 30.16% of the College students reported do not have a Religion, a higher percentage than that found by the National Census. Participants that do not have a religion present a higher chance to consume alcohol and binge drink. Having a religion may be a protection factor to binge drinking, especially, among evangelical participants.
Alcohol consumption among college students: history of violence as risk and religion as protective factor
Keywords: Psicologia; Álcool; Estudantes universitários; Violência; Alcohol; College students; History of violence; CIENCIAS HUMANAS::PSICOLOGIA